Lost in Translation: the Verbal Change from "Persona" to "Person" - Wu, Tzung-Mou (Instytut Językoznawstwa Wydział Neofilologii, UAM, 2010)
This paper challenges the modern legal concept of "person" by analyzing the translation problems of some Roman law fragments. It shows why the Latin word "persona" cannot be the etymon of the vernacular "person", and argues that the modern use of "person" stems from the nineteenth-century German juridical literature, especially that of F. C. von Savigny. This paper shows that "persona" forms a phrase with verbs like gerere, tenere and sustinere (bear, carry, hold, etc.) and has no meaning by itself. Such phrases require a noun complement in genitive form, as their synonym "represent", which is transitive, needs a direct object. On the other hand, the modern literature attributes a sense to "person", taking it as equivalent to "human individual" and using it word with the verb "be". This use is a modern invention and cannot be re-translated into Latin without semantic confusion.

Cet article met en cause le concept juridique moderne de «personne» en analysant les problèmes de traduction de quelques fragments de droit romain. L'article explique pourquoi le mot latin «persona» ne peut pas être l'étymon du mot vernaculaire «personne», et que l'emploi moderne de «personne» remonte à la littérature juridique allemande de XIXe siècle, en particulier des écrits de F. C. von Savigny. Cet article constate que «persona» fait partie des expressions idiomatiques construites avec des verbes tels que gerere, tenere et sustinere (porter, tenir, supporter, etc.) et n'a pas de signification en lui-même. Ce genre d'expression a besoin d'un substantif en génitif comme complément, tout comme leur synonyme «représenter», qui est transitif, nécessite un complément d'objet direct. De l'autre cóté, la littérature moderne attribue un sens au «personne», le traitant comme équivalent de l' «individu humain» et l'employant avec le verbe «être». Cet emploi est une invention moderne et ne peu se retraduire en latin sans perplexité sémantique.
Utracone w przekładzie: zmiana werbalna z "osobistości" w "osobę"